2016
DOI: 10.3390/s16050646
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Sleep Measures from Four Personal Health Monitoring Devices Compared to Research-Based Actigraphy and Polysomnography

Abstract: Polysomnography (PSG) is the “gold standard” for monitoring sleep. Alternatives to PSG are of interest for clinical, research, and personal use. Wrist-worn actigraph devices have been utilized in research settings for measures of sleep for over two decades. Whether sleep measures from commercially available devices are similarly valid is unknown. We sought to determine the validity of five wearable devices: Basis Health Tracker, Misfit Shine, Fitbit Flex, Withings Pulse O2, and a research-based actigraph, Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
187
4
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(203 citation statements)
references
References 26 publications
7
187
4
5
Order By: Relevance
“…Although not many validation studies have been performed on fitness activity trackers in the domain of sleep, this demonstration of an overestimation for total sleep time and inability to accurately identify wake epochs has been corroborated by studies on women with insomnia (de Zambotti et al, 2015) and adolescents referred for clinical PSG (Meltzer et al, 2015). Contrary to the results of these investigations, one study in healthy, young adults demonstrated comparable results in estimation of total sleep time for multiple fitness activity trackers, relative to PSG (Mantua et al, 2016). However, because epoch-by-epoch comparisons were not performed, the full performance characteristics of the fitness trackers utilized in this study, relative to PSG, could not be determined.…”
Section: Introductioncontrasting
confidence: 56%
“…Although not many validation studies have been performed on fitness activity trackers in the domain of sleep, this demonstration of an overestimation for total sleep time and inability to accurately identify wake epochs has been corroborated by studies on women with insomnia (de Zambotti et al, 2015) and adolescents referred for clinical PSG (Meltzer et al, 2015). Contrary to the results of these investigations, one study in healthy, young adults demonstrated comparable results in estimation of total sleep time for multiple fitness activity trackers, relative to PSG (Mantua et al, 2016). However, because epoch-by-epoch comparisons were not performed, the full performance characteristics of the fitness trackers utilized in this study, relative to PSG, could not be determined.…”
Section: Introductioncontrasting
confidence: 56%
“…The Fitbit® Flex™ can be used to measure sleep, as long as the user is aware that the data collected point to an overestimation of sleep duration and quality. Consequently, our measurements of sleep duration and quality, which are already low, may have been overestimated [15]. …”
Section: Discussionmentioning
confidence: 99%
“…A comparison of these and similar commercial personal health monitoring devices against global sleep measures (via PSG) in healthy populations has found no significant differences between them in terms of the their ability to estimate total sleep time [41]. However, it is reasonable to assume that a simple in/out of bed sensor may provide similar accuracy levels in terms of total sleep time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An epoch-by-epoch comparison is necessary to provide a more rigorous evaluation of the performance of these systems. Furthermore, healthy adult users were found to be unreliable for any devices which required the user to initiate a sleep tracking setting [41]. Therefore, when moving to long-term sleep monitoring, particularly in populations with potential memory issues, an ambient technology requiring no user interaction is desirable.…”
Section: Literature Reviewmentioning
confidence: 99%